2005
DOI: 10.1124/mol.105.018770
|View full text |Cite
|
Sign up to set email alerts
|

Ester Derivatives of Tournefolic Acid B Attenuate N-Methyl-d-aspartate-Mediated Excitotoxicity in Rat Cortical Neurons

Abstract: The effects of tournefolic acid B (TAB) and two ester derivatives, TAB methyl ester (TABM) and TAB ethyl ester (TABE), on N-methyl-D-aspartate (NMDA)-mediated excitotoxicity and the underlying mechanisms were investigated. Treatment with 50 M NMDA elicited neuronal death by 48.7 Ϯ 5.1%, coinciding with the appearance of injured morphology. TABM (50 M) attenuated the NMDA-induced cell death by 60.9 Ϯ 19.7%, and to a lesser extent by TABE. The NMDA-mediated activation of calpain was not affected by TABM and TABE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A previous study has demonstrated acute increases in ER Ca 2+ levels following NMDA receptor activation (Wang et al. 2006).…”
Section: Discussionmentioning
confidence: 96%
“…A previous study has demonstrated acute increases in ER Ca 2+ levels following NMDA receptor activation (Wang et al. 2006).…”
Section: Discussionmentioning
confidence: 96%
“…activated by LPS to produce NO were used to evaluate the antineuroinflammatory effects of the compounds. 25,26 Results of this assay revealed that 13 compounds (5,11,17,20,24,27,28,29,34,37,38,42, and 43) possessed antineuroinflammatory activities and compounds 24, 34, 37, and 38 were the most active (Tables 3 and 4). APP/PS1 mice obtained lower nesting scores and presented less nestlet shredding than did WT mice.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that TAB and LSA derivatives effectively attenuate neurotoxicity mediated by Aβ, glutamate, NMDA, and 1-methyl-4-phenylpyridinium. Specifically, TAB and LSA achieve this by abrogating calcium overload in mitochondria and retarding the caspase 8-truncated bid–cytochrome c pathway. Other polyphenols, such as resveratrol (a natural compound with stilbene structure), have also been studied extensively as anti-AD agents because of their antineuroinflammatory properties and ability to inhibit Aβ aggregation by scavenging oxidants. Therefore, we hypothesize that polyphenolic compounds presenting antioxidant activity could form the basis of novel treatments for AD. However, the TAB molecule comprises a seven-membered ring scaffold (belonging to the dibenzoxazepine class), which makes it difficult to synthesize.…”
Section: Introductionmentioning
confidence: 99%
“…The calpain-dependent cleavage of α-spectrin is involved in the death of primary cortical neurons, but not of CATH.a cells. The reason may be due to that CATH.a cells is not a neurite-bearing mature neurons [ 19 , 30 ] and which may explain why LSA fail to protect the primary cortical neurons against MPP + -mediated neuron death. The previous reports suggested that calpain plays a central role in MPP + mediates cell death in spinal cord motoneurons [ 31 ] and cerebellar granule neurons [ 32 ] may supported this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular level of O 2 − . was measured by dihydroethidium assay as described previously [ 19 ]. Treated cells were loaded with 3.2 μM dihydroethidium at 37 °C for 30 min and then observed by a Leica DMIRB fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%